PENGARUH PEMBERIAN EKSTRAK ETANOL BIJI MAHONI (SWIETENIA MAHAGONI) TERHADAP PENGHAMBATAN PERTUMBUHAN ESCHERICHIA COLI DENGAN METODE DIFUSI CAKRAM - AGNESSYA ESA OKTAVIA, GEBBY (Universitas Negeri Surabaya, 2013)
Escherichia coli is commonly known as nonpathogenic bacteria, but some strains are pathogenic and cause diarrhea, urinary tract infections, and meningitis. Escherichia coli is initially sensitive to antibiotics, but lately began resistant. Alternative antibacterial can be obtained from extracts of certain plants, such as mahogany (Swietenia mahogany). This research aimed to determine the effect of various concentrations of ethanolic extract of mahogany seeds to growth inhibition of  Escherichia coli FNCC 0091 and determine the concentration that could optimally inhibited the growth of Escherichia coli FNCC 0091. Mahogany seeds extract was prepared by maceration method with 96% ethanol. Antibacterial activity was done by disc diffusion method. Data obtained were diameter of clear zone. Data were analyzed using one-way analysis of variance followed by Duncan's test. Results showed that the ethanolic extract mahogany seeds could inhibited the growth of Escherichia coli FNCC 0091. The best treatment was ethanolic extract of mahagony seeds at concentration 100% and 80% with clear zone of 2.33 mm and 2.13 mm.     Key words: Escherichia coli FNCC 0091; ethanolic extract of mahogany seed; discs diffusion method